Tunable Mechanical Metamaterial with Constrained Negative Stiffness for Improved Quasi‐Static and Dynamic Energy Dissipation. Issue 7 (9th April 2019) - Morris, Clinton; Bekker, Logan; Spadaccini, Christopher; Haberman, Michael; Seepersad, Carolyn
Abstract : This paper presents the computational design, fabrication, and experimental validation of a mechanical metamaterial in which the damping of the material is significantly increased without decreasing the stiffness by embedding a small volume fraction of negative stiffness (NS) inclusions within it. Unlike other systems that dissipate energy primarily through large‐amplitude deformation of nonlinear structures, this metamaterial dissipates energy by amplifying linear strains in the viscoelastic host material. By macroscopically tuning the pre‐strain of the metamaterial via mechanical loading, the embedded NS inclusions operate about a constrained buckling instability. When further macroscopic vibrational excitation is applied, the inclusions amplify the strains of the surrounding viscoelastic medium. This results in enhanced dissipation of mechanical energy when compared to voided or neat comparison media. Microstereolithography, an emerging high‐resolution additive manufacturing (AM) technology, is employed to fabricate the deeply subwavelength inclusions which ensures broadband damping behavior. The mechanically induced broadband energy dissipation and manufacturing approach further differentiate the metamaterial from other approaches that exploit resonances, large deformations, or non‐mechanical instabilities. The computational design, fabrication, and experimental evaluation reported is the first dynamic demonstration of such a mechanically tunable NS metamaterial, potentially enabling components with integrated structural and damping capabilities. Abstract : This paper presents the computational design, fabrication, and experimental validation of a mechanical metamaterial in which the mechanical damping of the material is significantly increased by embedding a small volume fraction of negative stiffness (NS) inclusions within it. Unlike other acoustic metamaterials that exploit resonances to enhance damping, the passive mechanical damping reported here occurs across a broad band of frequencies, including quasi‐static deformation.